Novel fast-acting pyrazole/pyridine-functionalized N-heterocyclic carbene silver complexes assembled with nanoparticles show enhanced safety and efficacy as anticancer therapeutics. Issue 8 (5th February 2020) - Chen, Chao; Zhou, Liqian; Xie, Binbin; Wang, Yuchen; Ren, Lulu; Chen, Xiaona; Cen, Beini; Lv, He; Wang, Hangxiang
Abstract : Four multi-nuclear silver complexes with pyrazole/pyridine-functionalized NHC ligands were synthesized and characterized. The anticancer activity of these silver complexes was investigated both in vitro and in vivo . Abstract : In this study, we designed and synthesized four novel multi-nuclear silver complexes (1–4 ) coordinated with pyrazole- or pyridine-functionalized N-heterocyclic carbene (NHC) ligands. The crystal structures of the silver–NHC complexes were confirmed by X-ray diffraction analysis. In vitro assays showed that the silver–NHC complexes effectively killed a broad range of cancer cells after short-term drug exposure, serving as fast-acting cytotoxic agents. Of note, in cisplatin-resistant A549 cancer cells, the silver complexes were not cross-resistant with the clinically used cisplatin agent. Detailed mechanistic studies revealed that complex 2 triggered caspase-independent cell necrosis associated with intracellular reactive oxygen species (ROS) production and mitochondrial membrane potential (MMP) depletion. By exploiting a facile nano-assembly process, silver–NHC complexes 1, 2 and 4 were successfully integrated into the hydrophobic cores of amphiphilic matrices (DSPE-PEG2K ), enabling systemic injection. The silver complex-loaded nanotherapeutics (1 -NPs, 2 -NPs, and 4 -NPs) showed high safety margins with reduced systemic drug toxicities relative to cisplatin in animals. Furthermore, in a xenograft model of human colorectal cancer, the administration of the nanotherapeutics resulted in a marked inhibition of tumor progression.